Reported Sexual Violence among Women and Children Seen at the Gynecological Emergency Unit of a Rural Tertiary Health Facility, Northwest Nigeria - Ashimi, AO (Ann Med Health Sci Res, 2015)
BACKGROUND: Various forms of sexual violence including: Coerced marriage or wife inheritance, female genital mutilation, forced exposure to pornography, rape by intimate partner or strangers, unwanted sexual advances, and sexual abuse occurs, especially in vulnerable groups. However, most of these cases are not reported. AIM: The aim was to review reported cases in the facility, determine the prevalence and pattern of presentation. SUBJECTS AND METHODS: This was a prospective longitudinal study undertaken at the Gynecological Emergency Unit of a Tertiary Health Facility in a rural setting Northwest Nigeria. A study of survivors of alleged sexual violence who presented to the hospital from the September 1, 2011 to August 31, 2013. RESULTS: During the study period, there were 24 cases of sexual violence (22 were alleged rape and 2 were others) of 973 gynecological consultations at the emergency unit, giving a prevalence of 3% (24/973) for sexual violence and 2.3% (22/973) for alleged rape. Majority 91.7% (22/24) of the cases were children < 16 years; 45.8% (11/24) had no formal education while 33.3% (8/24) hawked homemade drinks and snacks. The assailants were known in 83.3% (20/24) of the cases; of which 45.8% (11/24) were neighbors, 29.2% (7/24) were buyers of snacks and drinks while 8.3% (2/24) were family members. CONCLUSION: The prevalence of reported sexual violence in this facility was low with the majority of the survivors being children and nonstranger assailants’, mostly neighbors.